The Theory of Being and the Argument for Forms in Plato’s Sophist - Leigh, Fiona (Phronesis, 2024)
This paper argues for two claims. First, that in the Sophist a metaphysical theory of being is constructed from the ground up, largely on the basis of a claim treated as an axiomatic principle, the ‘dunamis proposal’ (247d–e), which, I will argue, ought to be understood as Plato’s own definition of being. Second, once its core is in place, the theory is put to use to provide dialectical arguments against proponents of alternative metaphysical theories for the existence of various entities in the ontology. These include—notably—an argument for the existence of Forms.